Development of antenatal psychosocial stress scale for pregnant women in Kerala, India - Devisree, R.; Nirmala, C.; Indu, P. S.; Remadevi, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Psychosocial stress in pregnancy, defined as, “the imbalance that a pregnant woman feels when she cannot cope with demands is expressed both behaviourally and physiologically”. The purpose of this study was to develop a culturally appropriate and locally relevant scale for measuring antenatal psychosocial stress. Methods: Cross sectional design was used for the study. Participants were antenatal women attending outpatient department of both government and private sector. Twenty-nine item questionnaires to identify psychosocial stress among antenatal women was developed by conducting focus group discussions and in-depth interviews among socioeconomically diverse population and different parity and among uncomplicated and complicated pregnancies. By administering the questionnaire among 190 participants, Reliability and Validity were estimated. Factor analysis was done for item reduction. Poor loading, wrong loading and cross loading items were removed from the questionnaire. Convergent validity assessed with prenatal psychosocial stress scale among 55 antenatal women. Results: The final questionnaire has 10 items. Item-total correlation was found to be greater than 0.2 for all the items. The internal consistency coefficient (Cronbach’s alpha) for the 29-item questionnaire was 0.878. Test-retest reliability was 0.98 (95% CI 0.96-0.99). Further, factor analysis was done to demonstrate construct validity. The interrater reliability was 0.98 (95% CI- 0.96-0.99). Conclusions: Based on analysis of psychometric properties, the conclusion is that the 10 items questionnaire is a reliable, simple, valid and easy to administer tool for use among antenatal women of all settings.